Brief Considerations On The Fundamental Right To Vote In Romania (Discourse of Law and Administration, 2022)
The rights and fundamental freedoms of humans and citizens are a constitutional reality, with deep implications in the existence of every person, in his relations with the state. It also represents an existential reality of every person, of the society as an ensemble and a dimension of democracy. A category of the rights and fundamental freedoms is represented by the exclusively political rights. These fundamental rights refer only to Romanian citizens and have as object the participation of citizens in the management of the state and in governance. The Romanian Constitution refers to two of them (the right to vote and the right to be elected), which represent human rights, essence of constitutionality and proclaimed by the first documents with constitutional value, but also to a third right, newly inserted by the revision of 2003: the right to choose and be elected in the European Parliament. These are the means by which the people, as owner of the sovereignty, participates in the exercise of power in the state.
Keywords: rights and fundamental freedoms; human rights; right to vote